Islamic Revivalism in Recent Western Writings (American Journal of Islam and Society, 1994)
This article revolves atound certain presuppositions, themes, andthmries related to a selected number of westem writings on Islamic nxurgencein the m&m Arab world. In this regard, I purport to examine thefollowing claims: 1) Islamic resurgence is a widespread traditional, cultural,and political phenomenon in modem Islam; 2) some westem (andeven Muslim) studies of Islamic TesuTgence have touched only the surfaceand, therefore, their methodological orientation has been inadequak, 3)as a facet of modem Islam, Islamic resurgence has reinterpreted theIslamic tradition in a creative and unique way; and 4) although the majorleaders of the Islamic movement have placed philosophy outside the paleof Islam, one is tempted to study Islamic resurgence as a philosophicalexpression of modem and contemporary Muslim Societies.'In order to show the theoretical inadequacy of the writings on Islamictevivalism, I would like to discuss four Fecently published studies:Emmanuel Sivan, Radical Islam: Medieval Theology and Modern Politic?W. Montgomery Watt, Islamic Fundamentalism and Moderniq;Leanard Binder, Islamic Liberalism: A Critique of Development Ideologied;and Ronald Nettler, Past Trials and Present Tiibulation.In Radical Islam, Sivan proposes the following two ideas: First, tohave a better understanding of the thinking of modem Islamic resurgence,especially that of Sayyid Qutb," one has to study the influence exerted ...